General practice and genomics. Issue 2 (February 2017) - Rafi, Imran; Hayward, Judith; Alberg, Corinna
Clinicians have always personalised patient management. There is a growing momentum to improve this further through the integration of genomic information into clinical care. This will incorporate powerful new tools, through which clinicians can further tailor healthcare, improving disease prevention, prediction, diagnosis and treatment. This article aims to suggest ways in which this revolution in healthcare will affect GPs.